2013
DOI: 10.4103/2231-0738.119840
|View full text |Cite
|
Sign up to set email alerts
|

Role of measurement of blood ketone bodies in the management of diabetic ketoacidosis

Abstract: Objective:The present study was designed to investigate whether early detection of blood ketone bodies help in diagnosing Diabetic ketoacidosis (DKA) and also to explore whether early changes in blood β-hydroxybutyrate is associated with serum electrolytes and acid-base abnormalities. Research Design and Methods: A total of 122 consecutive type 2 diabetic patients (age 39 ± 15 yrs and body mass index 20.3 ± 2.4 kg/m 2 , mean ± SD) were included in the study. Plasma glucose was measured by glucose oxidase metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The results of this study was in line with our study results. 12 Hirobata et al in another study showed that Serum ketone body levels were negatively correlated with the levels of blood HCO3 -and pH which was in line with our study results because in this study we found that this correlation was negative and significant. 13…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study was in line with our study results. 12 Hirobata et al in another study showed that Serum ketone body levels were negatively correlated with the levels of blood HCO3 -and pH which was in line with our study results because in this study we found that this correlation was negative and significant. 13…”
Section: Discussionsupporting
confidence: 93%
“…The search identified nine studies that met the inclusion criteria of which: one compared capillary β-OHB with blood glucose levels ≥10.0 mmols/L [ 4 ]; two compared capillary β-OHB with standard measures (arterial blood gases, anion gap and carbon dioxide) of DKA [ 23 , 24 ], although one did not include urine ketones [ 23 ]; one compared capillary β-OHB with the manual enzymatic method [ 25 ]; five compared capillary β-OHB with urine ketones in detecting DKA [ 6 , 14 , 25 , 26 , 27 ] (refer to Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The studies included a total of 2019 participants, with a range of 19–529. Studies were completed in Australia [ 9 ], Banglaesh [ 27 ], France [ 14 ], Greece [ 25 ], Singapore [ 24 ], South Africa [ 28 ], Thailand [ 6 ], and USA [ 23 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation